Eliciting health state utilities for Dupuytren’s contracture using a discrete choice experiment - Gu, Ning Yan (Informa Healthcare, 2013)
BACKGROUND AND PURPOSE: An internet-based discrete choice experiment (DCE) was conducted to elicit preferences for a wide range of Dupuytren’s contracture (DC)-related health states. An algorithm was subsequently developed to convert these preferences into health state utilities that can be used to assess DC’s impact on quality of life and the value of its treatments. METHODS: Health state preferences for varying levels of DC hand severity were elicited via an internet survey from a sample of the UK adult population. Severity levels were defined using a combination of contractures (0, 45, or 90 degrees) in 8 proximal interphalangeal and metacarpophalangeal joints of the index, middle, ring, and little fingers. Right-handed, left-handed, and ambidextrous respondents indicated which hand was preferable in each of the 10 randomly-selected hand-pairings comparing different DC severity levels. For consistency across comparisons, anatomically precise digital hand drawings were used. To anchor preferences onto the traditional 0–1 utility scale used in health economic evaluations, unaffected hands were assigned a utility of 1.0 whereas the utility for a maximally affected hand (i.e., all 8 joints set at 90 degrees of contracture) was derived by asking respondents to indicate what combination of attributes and levels of the EQ-5D-5L profile most accurately reflects the impact of living with such hand. Conditional logistic models were used to estimate indirect utilities, then rescaled to the anchor points on the EQ-5D-5L. RESULTS: Estimated utilities based on the responses of 1,745 qualified respondents were 0.49, 0.57, and 0.63 for completely affected dominant hands, non-dominant hands, or ambidextrous hands, respectively. Utility for a dominant hand with 90-degree contracture in t h e metacarpophalangeal joints of the ring and little fingers was estimated to be 0.89. Separately, reducing the contracture of metacarpophalangeal joint for a little finger from 50 to 12 degrees would improve utility by 0.02. INTERPRETATION: DC is associated with substantial utility decre- ments. The algorithms presented herein provide a robust and flexible framework to assess utility for varying degrees of DC severity.